DEVELOPMENT OF DISCOVERY LEARNING-BASED E-MODULES TO IMPROVE CONCEPT UNDERSTANDING ABILITY IN FLAT BUILDING MATERIALS - Ramli Ramli (Indonesian Journal of Multidisciplinary Science, 2022)
This study uses reseach and development methods wuth the ADDIE development model consisting of five stages which include analysis, design, development, implementation, and evaluation. The reseach aims to produce electronic-based teaching materials (E-Modul) on the ability to understand student’s mathematical concepts on flat-shaped materials. The quality of the teaching materials developed is reviewed from three aspect, namely validity, practicality, and effectiveness. Assessment of the validity of this e-module teaching material is carried out by media experts and material experts, the result show that the teaching materials developed are valid with a value of 85,9% and meet the criteria for use. The results of the questionnaire analysis of theacher responses and student responses show that the teaching materials used are practical with the ideal percentages of 90,6% and 89,4% resvectively, and scores of 4,53 and 4,47 which indicate practical e-mudule teaching materials to be thaught use. As well as the use of e- module teaching materials in effective learning to improve student’s ability to understand mathematical concepts with the result of the analysis of the mean T- count 12,135 greater than T-table 1,697 and 76,47% of students being able to achieve the KKM score.